1986
DOI: 10.1212/wnl.36.3.340
|View full text |Cite
|
Sign up to set email alerts
|

Why do frontal lobe symptoms predominate in vascular dementia with lacunes?

Abstract: We studied 30 necropsy cases of vascular dementia with a lacunar state. Manifestations included dementia, lack of volition, emotional lability, small-stepped gait, dysarthria, urinary incontinence, grasp reflex, pyramidal signs, paraplegia in flexion, and akinetic mutism. Pathologically, there was diffuse incomplete softening of white matter in all cases. Both lacunes and diffuse softening were found predominantly in the frontal lobes. The prominent clinical features were therefore frontal lobe symptoms, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
4

Year Published

1987
1987
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(64 citation statements)
references
References 0 publications
4
56
0
4
Order By: Relevance
“…Compared to patients with AD, VaD patients suffer severe WM damage, arteriosclerosis-like changes, WM vacuolization and demyelination particularly in the periventricular region (Erkinjuntti, et al, 1996). Also, the periventricular frontal lobe and caudate head suffers from the highest density and frequency of lacunar infarction (Ishii, et al, 1986). This periventricular WM damage which disrupts the neuronal connections to the frontal lobe may be central to VaD induced cognitive deficits (Sultzer, et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to patients with AD, VaD patients suffer severe WM damage, arteriosclerosis-like changes, WM vacuolization and demyelination particularly in the periventricular region (Erkinjuntti, et al, 1996). Also, the periventricular frontal lobe and caudate head suffers from the highest density and frequency of lacunar infarction (Ishii, et al, 1986). This periventricular WM damage which disrupts the neuronal connections to the frontal lobe may be central to VaD induced cognitive deficits (Sultzer, et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although the ischemic lesions occur in diffuse and extensive. white matter in Binswanger's disease and multiple lacuna dementia, frontal white matter is preferentially and 200 severely affected (Ishii et al, 1986). Electron microscopy studies in Binswanger's disease have revealed a significant decrease of nerve fibers in the anterior white matter and the genu of the corpus callosum, but not in the splenium (Yamanouchi et aZ., 1989;.…”
Section: Discussionmentioning
confidence: 99%
“…Subcortical VaD incorporates two clinical entities – ‘Binswanger’s disease’ and ‘the lacunar state’ [21, 22, 23, 24, 25]. The ischaemic lesions in VaD affect especially the prefrontal subcortical circuit [26], which explains the main cognitive, behavioural and clinical neurological features.…”
Section: Subcortical Vascular Dementiamentioning
confidence: 99%